ANALISIS PROSES BERPIKIR KOMBINATORIK SISWA DALAM MENYELESAIKAN PERMASALAHAN SPLTV DITINJAU DARI GAYA BELAJAR AUDITORIAL - Manohara, Nalayuswasti Yatna; Setiawani, Susi; Oktavianingtyas, Ervin (Kadikma, 2019)
This study aims to determine the student combinatorial thinking process in solving SPLTV problems. The research subjects were 5 auditory students in class X BIC 1 MAN 1 Jember. Data collection methods used are tests and interviews. Based on data analysis, the results of the study indicate that auditory students are able to use the concept and competence to provide combinatorial reasoning. At the stage of investigation the case students able to explain information, at the stage of calculating all cases, being able to write information using symbols but not being able to write down what was asked about the problem using symbols. At the systematic stage of generating a case, being able to make a plan so as to find a solution. At the stage of changing the problem into other combinatorial, able to find solutions more than one method or more than one method but there are students who have not been able to find solutions more than one method or more than one method, able to describe the reason or cause of the solution obtained. Keywords: Combinatorial thinking, SPLTV, Auditory learning style.